New agronomic approaches for abiotic stress management - Singh, Yogeshwar (Indian Farming, 2021)
As climate change affects input availability, especially water in many places, input use efficiency must increase with the productivity. Innovations in agriculture have always been important and will be even more vital in the context of climate change. Diffusion of the appropriate agricultural technologies will be crucial in enabling an effective technological response. Seeing the reliance of the poor on agriculture and the sensitivity of agriculture to climate change, the agricultural research should maintain its pace to provide the need based suitable technologies to achieve the goals of sustainable development.